Generation of synthetic megavoltage CT for MRI‐only radiotherapy treatment planning using a 3D deep convolutional neural network. Issue 10 (8th August 2022) - Scholey, Jessica E.; Rajagopal, Abhejit; Vasquez, Elena Grace; Sudhyadhom, Atchar; Larson, Peder Eric Zufall
Abstract: Background: Megavoltage computed tomography (MVCT) has been implemented on many radiotherapy treatment machines for on‐board anatomical visualization, localization, and adaptive dose calculation. Implementing an MR‐only workflow by synthesizing MVCT from magnetic resonance imaging (MRI) would offer numerous advantages for treatment planning and online adaptation. Purpose: In this work, we sought to synthesize MVCT (sMVCT) datasets from MRI using deep learning to demonstrate the feasibility of MRI‐MVCT only treatment planning. Methods: MVCTs and T1‐weighted MRIs for 120 patients treated for head‐and‐neck cancer were retrospectively acquired and co‐registered. A deep neural network based on a fully‐convolutional 3D U‐Net architecture was implemented to map MRI intensity to MVCT HU. Input to the model were volumetric patches generated from paired MRI and MVCT datasets. The U‐Net was initialized with random parameters and trained on a mean absolute error (MAE) objective function. Model accuracy was evaluated on 18 withheld test exams. sMVCTs were compared to respective MVCTs. Intensity‐modulated volumetric radiotherapy (IMRT) plans were generated on MVCTs of four different disease sites and compared to plans calculated onto corresponding sMVCTs using the gamma metric and dose‐volume‐histograms (DVHs). Results: MAE values between sMVCT and MVCT datasets were 93.3 ± 27.5, 78.2 ± 27.5, and 138.0 ± 43.4 HU for whole body, soft tissue, and bone volumes, respectively. Overall, there was good agreement between sMVCT and MVCT, with bone and air posing the greatest challenges. The retrospective dataset introduced additional deviations due to sinus filling or tumor growth/shrinkage between scans, differences in external contours due to variability in patient positioning, or when immobilization devices were absent from diagnostic MRIs. Dose distributions of IMRT plans evaluated for four test cases showed close agreement between sMVCT and MVCT images when evaluated using DVHs and gamma dose metrics, which averaged to 98.9 ± 1.0% and 96.8 ± 2.6% analyzed at 3%/3 mm and 2%/2 mm, respectively. Conclusions: MVCT datasets can be generated from T1‐weighted MRI using a 3D deep convolutional neural network with dose calculation on a sample sMVCT in close agreement with the MVCT. These results demonstrate the feasibility of using MRI‐derived sMVCT in an MR‐only treatment planning workflow.